Decarboxylative Umpolung of conjugated enals to β-carbanions for intramolecular nucleophilic addition to an aldehyde. Issue 8 (17th May 2017) - Liu, Feng; Tian, Jiaxin; Liu, Yong; Tao, Chuangan; Zhu, Hao; Zhang, Aina; Xu, Dongfang; Zhao, Baoguo
Abstract : Decarboxylative Umpolung converts enals to β-carbanions for intramolecular nucleophilic addition to an aldehyde group with excellent regio- and diastereoselectivities. Abstract : An interesting Umpolung strategy to generate β-carbanion equivalents from a conjugated enal has been developed. The enal group of compounds7 was chemospecifically converted to a delocalized carbanion by decarboxylation of the in situ formed imine between the enal and 2, 2-diphenylglycine (2 ), which then underwent nucleophilic addition at the β position of the enal to an intramolecular aldehyde group to give cyclized products8 in 54–93% yields.